Demand Elasticity on the Transport Market - Perić, Teodor; Štrumberger, Nada (Promet - Traffic&Transportation, 2002)
The elasticity of demand for traffic se1vices is the adaptationof traffic supply to traffic demand. The elasticity of suchdemand is low which is specific of the transport market, especiallyfrom the aspect of designing traffic demand.The essence of the problem of low elasticity can be noticedin three basic properties:First, in the change of place which determines the traffic demandor traffic relation.Second is the continuity of the need to transport goods andpassengers.Third, the needs for transport may vmy according to thechanges in society and economy, and they also change thesources of traffic demand. Therefore, the elasticity of demandfor traffic se1vices is relatively low.